Mapping Waves of Climate Contention: Tactical Shifts and Spatial Inequalities in the Italian Protest Cycle - Galiano, Angelo; Giannini, Vito (PARTECIPAZIONE E CONFLITTO, 2026)
This article analyses recent climate contention in Italy through an original dataset of 186 protest events collected between 2022 and 2024 using Online Protest Event Analysis (OPEA). Drawing on social movement theory and the concept of waves of contention, it examines the temporal rhythms, repertorial transformations, and spatial configurations of contemporary climate mobilization. Findings reveal a cyclical and intermittent pattern of protest, marked by alternating phases of intensification, latency, and strategic recomposition. While demonstrative practices remain dominant, the period is characterized by the temporary strategic centrality of civil disobedience, driven primarily by Ultima Generazione, which selectively reconfigures protest repertoires without producing a generalized escalation of conflict. Spatially, climate contention is concentrated in the metropolitan centres of Northern and Central Italy, while more territorially embedded forms of environmental mobilization appear rooted in distinct place-based ecologies of contention. Overall, the Italian case is interpreted as a specific wave of contention nested within a broader cycle of environmental contention, shaped by tactical innovation, internal differentiation, and shifting political opportunities.